DETECTION METHOD FOR KIDNEY DISEASE - MAHALAKSHMI YERRAMILLI; MURTHY VSN YERRAMILLI (2020)
To provide a method, for estimating a glomerular filtration rate, and for diagnosing, predicting and determining progress of kidney disease.SOLUTION: There is disclosed a method for estimating a glomerular filtration rate (GFR) in an animal subject, and that is a method including: measuring a density of free SDMA within a blood sample from the subject; measuring a density of creatine within the blood sample from the subject; and comparing a value obtained from an equation including a product of the density of the creatine and the density of the free SDMA with one or a plurality of standard values having correlation with the glomerular filtration rate in the animal subject.SELECTED DRAWING: None 【課題】糸球体濾過量を推定する、ならびに、腎疾患の進行を診断、予測および決定する方法を提供する。【解決手段】動物対象における糸球体濾過量（ＧＦＲ）を推定する方法であって、対象からの血液サンプル中の遊離型ＳＤＭＡの濃度を測定すること、対象からの血液サンプル中のクレアチニンの濃度を測定すること、およびクレアチニンの濃度と遊離型ＳＤＭＡの濃度との積を含む方程式から得られる値を、動物対象における糸球体濾過量と相関がある１つまたは複数の標準値と比較することを含む方法。【選択図】なし